2021
DOI: 10.1016/j.compag.2021.106011
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision approach to characterize size and shape phenotypes of horticultural crops using high-throughput imagery

Abstract: For many horticultural crops, variation in quality (e.g., shape and size) contribute significantly to the crop's market value. Metrics characterizing less subjective harvest quantities (e.g., yield and total biomass) are routinely monitored. In contrast, metrics quantifying more subjective crop quality characteristics such as ideal size and shape remain difficult to characterize objectively at the production-scale due to the lack of modular technologies for high-throughput sensing and computation. Several hort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…Although visual evaluation is a widely used nondestructive method for grading and sorting in horticultural crops, utilization of high-throughput phenotyping platforms is essential to obtain robust, faster, and objective results [ 14 ]. Nowadays, quantitative measurement of these traits (color, size, shape, and surface texture) using image analysis is increasingly used in different horticultural crops [ 13 , 84 , 85 , 86 , 87 ].…”
Section: Applications Of Image-based High-throughput Phenotyping In H...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although visual evaluation is a widely used nondestructive method for grading and sorting in horticultural crops, utilization of high-throughput phenotyping platforms is essential to obtain robust, faster, and objective results [ 14 ]. Nowadays, quantitative measurement of these traits (color, size, shape, and surface texture) using image analysis is increasingly used in different horticultural crops [ 13 , 84 , 85 , 86 , 87 ].…”
Section: Applications Of Image-based High-throughput Phenotyping In H...mentioning
confidence: 99%
“…The application of computer vision for shape quantification using images of sweet potatoes has shown that shape features, length-to-width ratio, curvature, cross-section roundness, and cross-sectional diameters, are highly predictive of shape classes. A neural network-based shape classifier was able to predict marketable (high market value) and non-marketable sweet potato classes with 84.59% accuracy [ 13 ]. In most food industries, quality is mainly assessed by experts based on subjective evaluation, which is very slow and inconsistent.…”
Section: Applications Of Image-based High-throughput Phenotyping In H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Big Data Analytics (BDA) is the process of using sophisticated analytics on BD ( Ciccullo et al, 2022 ). The most current or potential applications of BD in vegetables, fruits and other plant-based sectors include optimal planting of fruit trees using data extracted from satellite and unmanned aerial vehicle imagery ( Saldana Ochoa and Guo, 2019 ), characterisation of size and shape phenotypes of horticultural crops using high throughput imagery ( Haque et al, 2021 ), improvement of controlled environment agriculture, such as soilless hydroponics and others for vegetable and fruit farming ( Ragaveena et al, 2021 ), and mitigating post-harvest losses and managing fruit and vegetable quality through machine learning ( Singh et al, 2022 ).…”
Section: Interconnection Between Vegetal and Digital Trendsmentioning
confidence: 99%
“…The main challenge for commercializing this vegetable is associated with its market value since it is strongly dependent on the qualitative characteristics of the roots, such as the shape 5 . Hence, consumers prefer products that have adequate commercial standards and good appearance.…”
Section: Introductionmentioning
confidence: 99%